2011
DOI: 10.1021/nl2030163
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Photonic Crystal Lasers

Abstract: The nanopillar photonic-crystal cavities are arranged in arrays with varying pitch and diameter in order to fine tune the resonant wavelength and Q factor. Each array contains 4 rows and 6 columns of devices. In each row, the radius is varied between 0.15·a and 0.2·a (where a is the inter-pillar pitch). In each column, the inter-pillar pitch is varied between 324 nm and 342 nm. This variation in pitch corresponds to resonant wavelengths between 950 nm and 1000 nm according to the normalized frequency calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
105
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 32 publications
0
105
0
Order By: Relevance
“…[27][28][29] These ordered arrays of nanowires behave as 2D PhCs, modifying the nanowire emission, 30 and even leading to lasing. 31 In this paper, we demonstrate the directional emission of heterostructures embedded in semiconductor nanowires forming a quasi-2D PhC using Fourier microscopy. This technique allows us to image the emission in the reciprocal space in which each coordinate corresponds to one direction of emission.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] These ordered arrays of nanowires behave as 2D PhCs, modifying the nanowire emission, 30 and even leading to lasing. 31 In this paper, we demonstrate the directional emission of heterostructures embedded in semiconductor nanowires forming a quasi-2D PhC using Fourier microscopy. This technique allows us to image the emission in the reciprocal space in which each coordinate corresponds to one direction of emission.…”
Section: Introductionmentioning
confidence: 99%
“…However, F p is actually inversely proportional to the effective size of the mode, V a /Γ k , where the mode-gain overlap factor Γ k is defined in Eq. (8) and describes the spatial overlap between the mode and the active region. Thus, if the mode is poorly confined, Γ k < < 1, F p will remain small, despite a small active region.…”
Section: Purcell Effect In Semiconductor Nanolasersmentioning
confidence: 99%
“…In the past decade, lasing has been demonstrated in numerous wavelength and sub-wavelength scale structures, including dielectric micro-discs [1][2][3][4], photonic crystals [5][6][7][8][9], nanowires [10,11] and nanorods [12], nano-membranes [13][14][15], micro-pillars [16][17][18], and metal-clad nano-cavities [19][20][21][22][23][24]. While all these devices enable fundamental research of various nanoscale phenomena [25][26][27], the design and analysis of nanolasers have focused almost exclusively on the optical mode, i.e., pure electromagnetic (EM) consideration, usually at 4.5 K, 77 K and room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Recently, Scofield et al reported single-mode lasing from a defect mode in an InGaAs photonic crystal consisting of a 2-dimensional array of InGaAs nanowires. [10] To circumvent the need for fabrication and manipulation of complicated optical structures, we concentrated our effort towards a simple, linear, Fabry-Perot nanowire laser, where the factors enabling single-mode lasing are short cavity length, small cross section and very high material gain. By reducing the nanowire size, the number of cavity modes within the gain bandwidth is dramatically reduced.…”
Section: Introductionmentioning
confidence: 99%